2017
DOI: 10.2106/jbjs.16.00749
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Use of CT Imaging for Osteoporosis Screening and Bone Density Assessment

Abstract: Direct HU measurement from diagnostic CT scans has the potential to be used opportunistically for osteoporosis screening, but in its current state it is not ready for clinical implementation. There is a lack of exchangeability among different machines that limits its broad applicability. Future research efforts should focus on identifying thresholds at specific anatomic regions in high-risk patients in order to have the greatest impact on patients. However, using diagnostic CT to infer region-specific osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 61 publications
5
129
1
2
Order By: Relevance
“…However, there are several studies showing the associations between BA by CT and BMD by DXA, or between BA by CT and vertebral fractures. (44) In this study, we found an association between prevalent VFs and CT-measured baseline kyphosis angle, and between incident VFs and increase in kyphosis angle. In addition, baseline kyphosis angle was associated with short-term VF incidence after adjustment for BA and prevalent VFs.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, there are several studies showing the associations between BA by CT and BMD by DXA, or between BA by CT and vertebral fractures. (44) In this study, we found an association between prevalent VFs and CT-measured baseline kyphosis angle, and between incident VFs and increase in kyphosis angle. In addition, baseline kyphosis angle was associated with short-term VF incidence after adjustment for BA and prevalent VFs.…”
Section: Discussionsupporting
confidence: 47%
“…Lastly, BA is not a standardized method of bone density measurement. However, there are several studies showing the associations between BA by CT and BMD by DXA, or between BA by CT and vertebral fractures …”
Section: Discussionmentioning
confidence: 99%
“…Although out of the scope of routine dental practice, the screening of CT and micro‐CT imaging of the mandible were demonstrated as effective screening tools (Chai et al, ; Yamashita‐Mikami et al, ). The possibilities of an early referral to the physician by screening the bone changes reflect the importance and the opportunistic use of the dental screenings (Gausden, Nwachukwu, Schreiber, Lorich, & Lane, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ease of identifying vertebral fractures in CT, assessment of vertebrae in axial sections only instead of sagittal sections are source of under diagnosis and under reporting of vertebral fractures and due to its high radiation burden: broutine use of CT for detecting fractures is not practical worldwide (Takada et al, 2013;Alacreu et al, 2017;Glinkowski et al, 2017;Gausden et al, 2017;Lee et al, 2017;Jager et al, 2010). Use of only lateral scout CT images has been proposed to be a reasonable middle path, thereby retaining the superior resolution of CT at a much lesser radiation dose (Muller, 2008;Takada, 2013;, but in comparative studies (Kim, 2012;Takada, 2013), cv were higher than visual semi quantitative assessment and higher than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ease of identifying vertebral fractures in computer tomography scanner (CT, TDM or CT scanner), assessment of vertebrae in axial sections only instead of sagittal sections are source of under diagnosis and under reporting of vertebral fractures (Lenchik et al, 2004;Bauer et al, 2006;Muller et al, 2008;Muller et al, 2008;Woo et al, 2008;Williams et al, 2009). The detection is improved by scanner using lateral vieuw or radio mode with limited success or sagital reconstructions (Genant et al, 1996;Muller, 2008;Kim et al, 2012;Oei et al, 2013;Takada et al, 1998;Takada et al, 2013;Alacreu et al, 2017;Glinkowski et al, 2017;Gausden et al, 2017;Lee et al, 2017) and some authors reported newly introduced automated detection and soft-ware assisted systems (Narloch et al, 2016;Burns et al, 2017 to osteoporosis, the scarcity of data available on osteoporosis and practically non-existence and lack of the data on vertebral fracture incidence in these region and countries (IOF study group, 2011).…”
Section: Introductionmentioning
confidence: 99%